Characteristics of clay minerals in soil particles from an argillic horizon of Alfisol in central China - Ndzana, Georges Martial; Huang, Li; Wang, Jin Bo; Zhang, Zhi Yi (Applied clay science, 2018)
The soil particles (<2000, 450–2000, 100–450 and 25–100nm) in an Alfisol were studied using inductively coupled plasma-optical emission spectroscopy (ICP-OES), conventional and synchrotron X-ray diffraction (XRD), fourier-transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TG) to investigate the mineral composition of clays and changes in crystalline structure in the particles of an argillic horizon. The results showed that the clay minerals in the particle fractions (<2000, 450–2000 and 100–450nm) were illite, kaolinite, vermiculite and a trace amount of hydroxy interlayered vermiculite and chlorite. In the nanoparticles (25–100nm), the main clay minerals were illite and kaolinite. The molar ratios of SiO2 to Al2O3 and SiO2 to R2O3 (Al2O3 and Fe2O3) were higher in the nanoparticles compared to other particle fractions. With decreasing particles size, kaolinite and vermiculite decreased gradually and illite increased. The Al-Mg-OH and Si–O–Si (Al) stretching modes of vermiculite were broadened in the 100–450nm particles and disappeared in nanoparticles while the hydroxyl group (OH) of clay minerals in the samples was reduced with decreasing particle fractions. The broadening of the band characteristics of clay minerals, the dehydration and dehydroxylation were less pronounced in particle fractions from the argillic horizon comparing to the topsoil. Clay minerals from 450 to 2000 and 100–450nm particle fractions were well ordered whereas illite and kaolinite were poorly ordered in nanoparticles of the argillic horizon. The “crystallinity” of clay minerals was weakly affected in the particle fractions of argillic horizon compared to topsoil. •With decreasing soil particle size (from 2000 to 25nm), kaolinite and vermiculite decreased and illite increased.•Illite and kaolinite were the main clay minerals in nanoparticles from argillic horizon.•Well crystallized clay minerals were found in large particles (>100nm) and poorly crystallized in nanoparticles.•The molar ratios of SiO2/Al2O3 were highest in the nanoparticles compared to other particle fractions.•The crystalline structure of clay minerals was less destroyed in the argillic horizon than topsoil.